Characterization of galactomannans extracted from seeds of Gleditsia triacanthos and Sophora japonica through shear and extensional rheology : comparison with guar gum and locust bean gum - Bourbon, A. I. (2010)
The rheological behaviour, under steady and dynamic shear and extensional conditions, of two nonconventional galactomannans isolated from Gleditsia triacanthos and Sophora japonica is determined and compared to those of locust bean gum and guar gum. The studied galactomannans exhibit shear-thinning behaviour in the range of concentrations and shear rates evaluated. For similar concentrations and shear rates, the guar gum exhibits the highest viscosities. Experimental data in steady shear was correlated with the Cross model, which provided a good description of viscosity shear rate data. Under oscillatory shear, all gum solutions exhibited a behaviour typical of random-coil polysaccharide solutions. The extensional rheology experiments showed that by increasing the polymer concentration and decreasing the temperature, the relaxation times, elastic moduli and rupture times increase. These findings lead to the conclusion that G. triacanthos and S. japonica galactomannans can be used as efficient thickening hydrocolloids as alternative to conventional galactomannans.